2003
DOI: 10.1523/jneurosci.23-06-01997.2003
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Resonance within the Somatosensory System: Effects of Noise on Evoked Field Potentials Elicited by Tactile Stimuli

Abstract: Stochastic resonance (SR) is commonly understood to be the enhancement, by noise, of the response of a system to a weak input signal. The aim of this study was to demonstrate the occurrence of SR in spinal and cortical evoked field potentials (EFPs) elicited by periodic tactile stimuli in the anesthetized cat. The electrodes were positioned in spinal and cortical somatosensory regions in which the largest negative EFPs were detected. The periodic tactile stimuli consisted of local skin displacements on the cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
52
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 35 publications
9
52
0
Order By: Relevance
“…Our present study as well as other studies published by Lugo et al (2012), Mendez-Balbuena et al (2012), Trenado et al (2014a, 2014b), and Malacuso et al (2000 suggest that in the near future it will be possible to develop and design new devices that enable the use of multisensory SR in the visuotactile modality for human sensorimotor enhancement and rehabilitation purposes. For instance, Mendez-Balbuena et al (2012) and Trenado et al (2014a) suggested that multisensory SR could be employed to improve visuomotor human performance in easy, noninvasive ways.…”
Section: Possible Applications In Neuropsychologysupporting
confidence: 71%
See 4 more Smart Citations
“…Our present study as well as other studies published by Lugo et al (2012), Mendez-Balbuena et al (2012), Trenado et al (2014a, 2014b), and Malacuso et al (2000 suggest that in the near future it will be possible to develop and design new devices that enable the use of multisensory SR in the visuotactile modality for human sensorimotor enhancement and rehabilitation purposes. For instance, Mendez-Balbuena et al (2012) and Trenado et al (2014a) suggested that multisensory SR could be employed to improve visuomotor human performance in easy, noninvasive ways.…”
Section: Possible Applications In Neuropsychologysupporting
confidence: 71%
“…We employed a sample of eight subjects, as in our previous study (Mendez-Balbuena et al 2012), because the results obtained here were also clear and consistent within and across subjects. To exclude cyclic ovarian effects on cortical excitability and oscillatory cortical activity, the female subjects were in different menstrual phases (Smith et al 2002).…”
Section: Subjectsmentioning
confidence: 83%
See 3 more Smart Citations